Analisis Kinerja Keuangan Pemerintah Provinsi Jambi dan Pengaruhnya terhadap Pertumbuhan Ekonomi - Mohar Mondes (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2016)
The purpose of this research is to analise government’s financial performance of Jambi Province. This research is using multiple linear regression to calculate and to see the effect of direct and indirect expenditure variable to the economic growth. This research is using secondary data that includes of local revenues, equalization funds, financial reception area, direct and indirect expenditure and also total expenditure of Jambi Province. This research is using verifikatif and kuantitatif analysis which is suite for analise fiscal autonomy degree, fiscal dependency of Jambi Province toward central government and also to find out whether the direct and indirect expenditure has effect to economic growth. Research results showed that Jambi Province’s DOF based on local revenue is 39,57%, placed in average condition, however if local revenue is add on DBH, it showed that the criteria is very good with 58,92%. The level of fiscal dependency 34,80% in average for years during observasion periode. By using multiple linear regression, the result showed that direct and indirect expenditure were positively and significantly effected to the economic growth of Jambi Province